Sustainable Lighting through Design and Energy Efficiency Consumption of Artificial Lighting in Educational Building. : Case Study : S Building, FTUI, Depok, Indonesia - Sejati, Rr. Nurindah Wiji; Dewi, Ova Candra (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This research aims to explore sustainable lighting methods that can enhance lighting quality and energy efficiency in educational buildings. The background recognizes the importance of visual comfort and lighting quality in educational settings and their significant impact on students' academic performance. The specific case study focuses on Building S at the Faculty of Engineering, University of Indonesia in Depok, Indonesia. The study integrates principles of sustainable artificial lighting, design strategies, and energy-efficient lighting technologies through an extensive review of relevant literature and analysis using Dialux simulations and energy consumption calculations. Three different lighting design strategies are explored: Strategy 1 incorporating LED pendant lights, reflective finishing materials, and lighting automation; Strategy 2 utilizing LED spotlights and automation; Strategy 3 involving LED recessed lights and automation. The results demonstrate that Strategy 1 provides the highest levels of illuminance and energy efficiency, surpassing both the existing lighting conditions and the other strategies. The implementation of LED technology and lighting automation significantly reduces energy consumption while simultaneously enhancing the quality of lighting. This study highlights the importance of visual comfort and energy efficiency in fostering an ideal learning atmosphere in educational facilities. In conclusion, Strategy 1 emerges as the optimal choice for achieving both improved lighting quality and energy conservation in educational buildings.